Heteropolyacid modified cerium-titanium composite oxide catalyst as well as preparation method and application thereof

By modifying the composite layer of heteropolyacid and sodium dodecylbenzenesulfonate on the cerium titanium composite oxide catalyst to form a stable composite modification layer, the problems of low efficiency and poor stability in the purification of CVOCs and NOx are solved, and efficient and stable synergistic purification effect is achieved.

CN119657185APending Publication Date: 2025-03-21YANTAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411908940.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing catalysts have problems with low synergistic catalytic efficiency, few surfactant sites and poor stability in purifying chlorine-containing volatile organic compounds (CVOCs) and nitrogen oxides (NOx).

Method used

A cerium-titanium composite oxide catalyst modified by heteropolyacid is used. The catalyst is supported by a mesoporous cerium-titanium composite oxide, and a composite modification layer of heteropolyacid and sodium dodecylbenzene sulfonate is formed by heat treatment.

Benefits of technology

This catalyst has a wide operating temperature range, excellent catalytic performance and good stability. It especially shows obvious advantages when synergistic purification of CVOCs and NOx, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205125670000081
    Figure BDA0005205125670000081
  • Figure BDA0005205125670000082
    Figure BDA0005205125670000082
  • Figure HDA0005205125680000011
    Figure HDA0005205125680000011
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and discloses a heteropolyacid modified cerium-titanium composite oxide catalyst as well as a preparation method and application thereof. The catalyst takes a mesoporous cerium-titanium composite oxide as a carrier, and a heteropolyacid and sodium dodecyl benzene sulfonate composite modification layer is loaded on the surface of the carrier. The preparation method comprises the following steps: dipping a mesoporous cerium-titanium composite oxide in a composite solution of heteropolyacid and sodium dodecyl benzene sulfonate, and then carrying out heat treatment to obtain the heteropolyacid modified cerium-titanium composite oxide catalyst. The catalyst disclosed by the invention can be used for purifying CVOCs and NOx, has a relatively wide working temperature range, excellent catalytic performance and good stability and poisoning resistance, particularly shows obvious advantages when being used for cooperatively purifying CVOCs and NOx, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a heteropolyacid-modified cerium-titanium composite oxide catalyst and a preparation method and application thereof. Background Art

[0002] With the acceleration of industrialization, air pollution is becoming increasingly serious, among which chlorinated volatile organic compounds (CVOCs) and nitrogen oxides (NOx) are one of the main pollutants. Traditional catalysts have problems such as low synergistic catalytic efficiency, few surface sites and poor stability in purifying CVOCs and NOx. Therefore, it is of great significance to develop a new catalyst that is efficient, stable and can synergistically purify CVOCs and NOx. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a heteropolyacid-modified cerium-titanium composite oxide catalyst, a preparation method and an application thereof in view of the deficiencies in the prior art. The catalyst can be used to purify CVOCs and NOx, has a wide operating temperature range, excellent catalytic performance, good stability and anti-poisoning ability, and especially shows obvious advantages in the coordinated purification of CVOCs and NOx, and has broad application prospects.

[0004] In order to solve the technical problem proposed by the present invention, the present invention provides a heteropolyacid-modified cerium-titanium composite oxide catalyst, which uses a mesoporous cerium-titanium composite oxide as a carrier and carries a composite modification layer of heteropolyacid and sodium dodecylbenzene sulfonate on the surface.

[0005] In the above scheme, the heteropoly acid-modified cerium-titanium composite oxide is obtained by immersing the mesoporous cerium-titanium composite oxide in a composite solution of heteropoly acid and sodium dodecylbenzene sulfonate and then performing heat treatment.

[0006] In the above scheme, the mesoporous cerium-titanium composite oxide is prepared by a chitosan template method, wherein the molar ratio of cerium to titanium is (0.1-0.5):1.

[0007] In the above scheme, the particle size of the mesoporous cerium-titanium composite oxide is 10-12 nm, and the specific surface area is 200-217 m 2 / g, pore volume is 0.4~0.5cm 3 / g, pore size is 5~25nm.

[0008] In the above scheme, the heteropoly acid is H3PW 12 O 40 、H4SiW 12 O 40 、H3PMo 12 O 40 One of them.

[0009] In the above scheme, the molar ratio of the heteropoly acid to sodium dodecylbenzene sulfonate is 1:(2-10).

[0010] In the above scheme, the particle size of the heteropolyacid-modified cerium-titanium composite oxide catalyst is 7 to 10 nm, and the specific surface area is 180 to 210 m 2 / g, pore volume is 0.3~0.5cm 3 / g, pore size is 10~20nm.

[0011] The present invention also provides a method for preparing a heteropolyacid-modified cerium-titanium composite oxide catalyst, comprising the following steps:

[0012] 1) dissolving sodium dodecylbenzene sulfonate (SDBS) in water to obtain a SDBS solution;

[0013] 2) dissolving the heteropoly acid in an ethanol aqueous solution to obtain a heteropoly acid solution, and adjusting the pH to 1 to 3;

[0014] 3) under stirring conditions, adding the SDBS solution dropwise into the heteropolyacid solution to form a heteropolyacid-SDBS complex solution;

[0015] 4) impregnating the mesoporous cerium-titanium composite oxide into the heteropoly acid-SDBS complex solution, stirring for reaction, separating the solid and the liquid, and drying the solid to obtain a catalyst precursor;

[0016] 5) The catalyst precursor is heat-treated in an air atmosphere to obtain a heteropolyacid-modified cerium-titanium composite oxide catalyst.

[0017] In the above scheme, the concentration of the SDBS solution is 0.01-0.1 mol / L.

[0018] In the above scheme, in step 2), the volume fraction of ethanol in the ethanol aqueous solution is 75-95%.

[0019] In the above scheme, the concentration of the heteropoly acid in the heteropoly acid solution is 0.001 to 0.05 mol / L.

[0020] In the above scheme, in step 2), phosphoric acid is used to adjust the pH, and the concentration of phosphoric acid is 0.1-1.0 mol / L.

[0021] In the above scheme, in step 3), the stirring rate is 200 to 1000 r / min, the dropping time is 10 to 20 min, and the stirring is continued for 1 to 2 h after the dropping is completed.

[0022] In the above scheme, the molar ratio of the heteropoly acid to the titanium in the mesoporous cerium-titanium composite oxide is (0.05-0.2):1.

[0023] In the above scheme, in step 4), the stirring rate of the stirring reaction is 200 to 1000 r / min, and the reaction time is 4 to 24 h.

[0024] In the above scheme, in step 4), the drying temperature is 60 to 100° C. and the drying time is 12 to 36 hours.

[0025] In the above scheme, in step 4), the heating rate of the heat treatment is 2 to 5°C / min, the heat treatment temperature is 400 to 600°C, and the holding time is 2 to 4h.

[0026] In the above scheme, the preparation method of the mesoporous cerium-titanium composite oxide comprises the following steps:

[0027] a) dissolving a cerium source and a titanium source in an ethanol solution to obtain a cerium-titanium mixed solution;

[0028] b) dissolving chitosan in acetic acid solution to obtain a chitosan solution;

[0029] c) adding the cerium-titanium mixed solution dropwise to the chitosan solution under stirring, stopping stirring, heating until a uniform foaming gel system is formed, and drying to obtain a cerium-titanium composite oxide precursor;

[0030] d) heat-treating the cerium-titanium composite oxide precursor in an air atmosphere to obtain a mesoporous cerium-titanium composite oxide.

[0031] Furthermore, the cerium source is one of cerium nitrate, cerium chloride and ammonium cerium sulfate.

[0032] Furthermore, the titanium source is one of tetraethyl titanate and titanyl sulfate.

[0033] Furthermore, in step a), the volume fraction of ethanol in the ethanol solution is 75-95%.

[0034] Furthermore, the ratio of the titanium source to the ethanol solution is 0.01 mol: (40-80) mL.

[0035] Furthermore, the volume fraction of acetic acid in the acetic acid solution is 1-5%.

[0036] Furthermore, the ratio of chitosan to acetic acid solution is 0.01mmol:(50-100)mL.

[0037] Furthermore, the molar ratio of the titanium source to chitosan is 1:(1-5).

[0038] Furthermore, in step c), the stirring rate is 200 to 1000 r / min, the dropping time is 10 to 20 min, and the stirring is continued for 1 to 3 h after the dropping is completed.

[0039] Furthermore, in step c), the heating temperature is 60-80° C. and the heating time is 12-24 hours.

[0040] Furthermore, in step c), the drying is freeze drying, the drying temperature is -40 to -20°C, and the drying time is 12 to 48 hours.

[0041] Furthermore, in step d), the heating rate of the heat treatment is 2-5°C / min, the heat treatment temperature is 400-600°C, and the holding time is 2-4h.

[0042] The present invention also provides an application of a heteropolyacid-modified cerium-titanium composite oxide catalyst in purifying CVOCs and / or NOx. The specific method is: loading the heteropolyacid-modified cerium-titanium composite oxide catalyst into a catalytic reactor, and catalytically purifying the gas containing CVOCs and / or NOx through the catalytic reactor.

[0043] In the above scheme, if the gas contains CVOCs, the concentration of CVOCs is 50 to 100 ppm.

[0044] Furthermore, the CVOCs is one of chlorobenzene, vinyl chloride and dichloromethane.

[0045] In the above scheme, if the gas contains NOx, the NOx concentration is 500 to 800 ppm.

[0046] In the above scheme, the catalytic temperature of the heteropolyacid-modified cerium-titanium composite oxide catalyst is 100-300°C, and the space velocity is 48000-60000h -1 .

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The present invention provides a heteropolyacid-modified cerium-titanium composite oxide catalyst, which is prepared by an innovative synthesis process. First, chitosan is used as a template to prepare a mesoporous cerium-titanium composite oxide as a carrier, and then an innovative preparation process of a heteropolyacid-SDBS composite modification layer is used to combine an SDBS surfactant with a heteropolyacid through a self-assembly process to form a stable complex, and the SDBS surfactant is successfully modified on the surface of the mesoporous cerium-titanium composite oxide carrier to form a heteropolyacid-SDBS composite modification layer, thereby obtaining a heteropolyacid-modified cerium-titanium composite oxide catalyst. In the synthesis process of the catalyst of the present invention, the material ratio and the synthesis process are precisely controlled to ensure that the crystal structure, morphology and catalytic performance of the catalyst are optimal, especially in the heat treatment step, the heating rate, the treatment temperature and the insulation time are precisely controlled to avoid the agglomeration of the carrier and the growth of the grains, thereby improving the specific surface area and catalytic activity of the catalyst. The mesoporous cerium-titanium composite oxide in the catalyst of the present invention provides abundant active sites and good pore structure for the adsorption and catalytic reaction of the heteropoly acid-SDBS composite. The heteropoly acid-SDBS composite modification layer enhances the adsorption and catalytic conversion ability of the catalyst for CVOCs and NOx, thereby achieving efficient catalytic performance and good stability of the catalyst. The catalyst can be used to purify CVOCs and NOx, has a wide operating temperature range, excellent catalytic performance, good stability and anti-poisoning ability, and also shows obvious advantages in the coordinated purification of CVOCs and NOx, providing a new solution for industrial waste gas purification and having broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The heteropolyacid-modified Ce prepared in Example 1 0.3 -SEM (left) and TEM (right) images of the Ti composite oxide catalyst.

[0050] Figure 2 The heteropolyacid-modified Ce prepared in Example 1 0.3 -XRD pattern of Ti composite oxide catalyst.

[0051] Figure 3 The heteropolyacid-modified Ce prepared in Example 1 0.3 -EDS pattern of Ti composite oxide catalyst. DETAILED DESCRIPTION

[0052] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0053] Example 1

[0054] A method for preparing a heteropolyacid-modified cerium-titanium composite oxide catalyst comprises the following steps:

[0055] Weigh 0.003 mol of cerium nitrate hexahydrate and 0.01 mol of tetraethyl titanate, dissolve them in 80 mL of 75% ethanol solution, stir evenly, and obtain Ce 0.3 -Ti mixed solution; 1g of chitosan with a molecular weight of 100000g / mol (deacetylation degree of 80%, 0.01mmol) was dissolved in 60mL of 2% acetic acid solution, stirred to dissolve, and a chitosan solution was obtained; Ce 0.3 The mixed solution of -Ti was slowly added dropwise to the chitosan solution for 15 minutes with stirring. After the addition was completed, stirring was continued for 2 hours. After stopping stirring, the mixture was heated in a water bath at 80°C for 24 hours to form a uniform foaming gel system. The gel system was freeze-dried at -20°C for 48 hours to obtain Ce 0.3 -Ti composite oxide precursor; the precursor was heated to 600°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 3 hours to obtain mesoporous Ce 0.3 -Ti composite oxide, after testing, its particle size is 10nm, and the specific surface area is 217m 2 / g, pore volume is 0.43cm 3 / g, pore size is 15nm;

[0056] Weigh 0.0025 mol sodium dodecylbenzene sulfonate (SDBS), dissolve it in 25 mL water, stir to dissolve, and obtain a 0.1 mol / L SDBS solution; weigh 0.0005 mol H3PW 12 O 40 , dissolve it in 50mL of 75% ethanol aqueous solution, stir and dissolve to obtain a heteropoly acid solution with a concentration of 0.0033mol / L, use 0.5mol / L phosphoric acid to adjust the pH of the solution to 2, so that the heteropoly acid maintains a stable molecular structure; under the condition of a stirring rate of 600 rpm, slowly add the SDBS solution to the heteropoly acid solution, the dropping time is 15 minutes, after the dropping is completed, continue to stir for 1.5 hours to form a heteropoly acid-SDBS complex solution; the mesoporous Ce prepared above 0.3 -Ti composite oxide was immersed in the heteropoly acid-SDBS composite solution, stirred at a stirring rate of 800 rpm for 12 hours, and then solid-liquid separation was performed, and the solid was dried at 80°C for 24 hours to obtain a catalyst precursor; finally, the catalyst precursor was heated to 500°C at a heating rate of 3°C / min in an air atmosphere and kept warm for 3 hours to obtain heteropoly acid-modified Ce 0.3 -Ti composite oxide catalyst, the particle size is 7nm, the specific surface area is 210m 2 / g, pore volume is 0.40cm 3 / g, pore size is 14nm.

[0057] Figure 1 The heteropolyacid-modified Ce prepared in Example 1 0.3 -Ti composite oxide catalyst SEM (left) and TEM (right), showing that the heteropoly acid modified Ce 0.3 -Ti composite oxide catalyst presents the morphology of uniformly dispersed nanoparticles without obvious agglomeration, indicating that it has good dispersibility.

[0058] Figure 2 The heteropolyacid-modified Ce prepared in Example 1 0.3 -Ti composite oxide catalyst XRD diagram, the figure also shows the cerium-titanium composite oxide prepared with different cerium-titanium ratios, the figure shows that Ce 0.1 The diffraction peaks of the Ti-Si composite oxide appeared at 25.3, 38.6, 48.0 and 55.1, corresponding to the characteristic diffraction peaks of (101), (112), (211) and (211) planes, respectively. No diffraction peaks caused by cerium oxide were detected, which may be due to the low Ce doping amount or its uniform dispersion. With the further increase of Ce content, the diffraction peaks related to titanium dioxide gradually weakened. When the molar ratio of Ce to Ti reached 0.3:1, all the diffraction peaks disappeared, indicating that the interaction between cerium and titanium promoted the amorphous nature of the catalyst sample. With the further increase of Ce ratio, a slight diffraction peak appeared at 28.5, corresponding to the (111) plane of cerium oxide (PDF#43-1002). Further HPW / Ce modified by phosphotungstic acid showed a strong positive correlation with the (101), (112), (211) and (211) planes. The diffraction peaks caused by cerium oxide were not detected, which may be due to the low Ce doping amount or its uniform dispersion. 0.3 -Ti composite oxide catalyst also did not detect the emergence of new diffraction peaks, the surface phosphotungstic acid was evenly dispersed in the catalyst.

[0059] Figure 3 The heteropolyacid-modified Ce prepared in Example 1 0.3 -The EDS image of the Ti composite oxide catalyst shows that the P, W, Ce, Ti and O elements are uniformly dispersed, proving the successful introduction of HPW, and no lattice diffraction fringes are detected, indicating the unstructured structure of the catalyst components, which is consistent with the XRD results.

[0060] Example 2

[0061] Weigh 0.002 mol of cerium chloride and 0.01 mol of tetraethyl titanate, dissolve them in 80 mL of 75% ethanol solution, stir evenly, and obtain Ce 0.2-Ti mixed solution; 1g of chitosan with a molecular weight of 100000g / mol (deacetylation degree of 80%, 0.01mmol) was dissolved in 100mL of 2% acetic acid solution, stirred to dissolve, and a chitosan solution was obtained; Ce 0.2 The mixed solution of -Ti was slowly added dropwise to the chitosan solution for 15 minutes with stirring. After the addition was completed, stirring was continued for 2 hours. After stopping stirring, the mixture was heated in a 70°C water bath for 18 hours to form a uniform foaming gel system. The gel system was freeze-dried at -40°C for 36 hours to obtain Ce 0.2 -Ti composite oxide precursor; the precursor was heated to 500°C at a heating rate of 3°C / min in an air atmosphere and kept at this temperature for 3 hours to obtain mesoporous Ce 0.2 -Ti composite oxide, after testing, its particle size is 12nm, and the specific surface area is 214m 2 / g, pore volume is 0.42cm 3 / g, pore size is 15nm;

[0062] Weigh 0.003 mol sodium dodecylbenzene sulfonate (SDBS), dissolve it in 30 mL water, stir and dissolve to obtain a 0.1 mol / L SDBS solution; weigh 0.0015 mol H3PMo 12 O 40 , dissolve it in 40mL of 75% ethanol aqueous solution, stir and dissolve to obtain a heteropoly acid solution with a concentration of 0.0375mol / L, use 0.3mol / L phosphoric acid to adjust the pH of the solution to 2 to keep the heteropoly acid in a stable molecular structure; under the condition of a stirring rate of 400 rpm, slowly add the SDBS solution to the heteropoly acid solution for 10 minutes. After the addition is completed, continue stirring for 2 hours to form a heteropoly acid-SDBS complex solution; the mesoporous Ce prepared above 0.2 -Ti composite oxide was immersed in the heteropoly acid-SDBS composite solution and stirred for 12 hours at a stirring rate of 800 rpm. Then solid-liquid separation was performed, and the solid was dried at 80°C for 24 hours to obtain a catalyst precursor; finally, the catalyst precursor was heated to 500°C at a heating rate of 3°C / min in an air atmosphere and kept warm for 3 hours to obtain heteropoly acid-modified Ce 0.2 -Ti composite oxide catalyst, the particle size is 10nm, the specific surface area is 206m 2 / g, pore volume is 0.4939cm 3 / g, pore size is 13nm.

[0063] Example 3

[0064] Weigh 0.005 mol of ammonium cerium sulfate and 0.01 mol of tetraethyl titanate, dissolve them in 80 mL of 75% ethanol solution, stir evenly, and obtain Ce 0.5 -Ti mixed solution; 1g of chitosan with a molecular weight of 100000g / mol (deacetylation degree of 80%, 0.01mmol) was dissolved in 100mL of 1% acetic acid solution by volume, and stirred to dissolve to obtain a chitosan solution; Ce 0.5 The mixed solution of -Ti was slowly added dropwise to the chitosan solution for 15 minutes with stirring. After the addition was completed, stirring was continued for 2 hours. After stopping stirring, the mixture was heated in a 70°C water bath for 18 hours to form a uniform foaming gel system. The gel system was freeze-dried at -30°C for 36 hours to obtain Ce 0.5 -Ti composite oxide precursor; the precursor was heated to 500°C at a heating rate of 3°C / min in an air atmosphere and kept at this temperature for 3 hours to obtain mesoporous Ce 0.5 -Ti composite oxide, after testing, its particle size is 11nm, and the specific surface area is 200m 2 / g, pore volume is 0.41cm 3 / g, pore size is 18nm;

[0065] Weigh 0.005 mol sodium dodecylbenzene sulfonate (SDBS), dissolve it in 50 mL water, stir to dissolve, and obtain a 0.1 mol / L SDBS solution; weigh 0.0005 mol H3PW 12 O 40 , dissolve it in 50mL of 75% ethanol aqueous solution, stir and dissolve to obtain a heteropoly acid solution with a concentration of 0.01mol / L, use 0.5mol / L phosphoric acid to adjust the pH of the solution to 2, so that the heteropoly acid maintains a stable molecular structure; under the condition of a stirring rate of 1000 rpm, slowly add the SDBS solution to the heteropoly acid solution for 15 minutes. After the addition is completed, continue stirring for 1.5 hours to form a heteropoly acid-SDBS complex solution; the mesoporous Ce prepared above 0.5 -Ti composite oxide was immersed in the heteropoly acid-SDBS composite solution, stirred at a stirring rate of 800 rpm for 12 hours, and then solid-liquid separation was performed, and the solid was dried at 80°C for 24 hours to obtain a catalyst precursor; finally, the catalyst precursor was heated to 500°C at a heating rate of 3°C / min in an air atmosphere and kept warm for 3 hours to obtain heteropoly acid-modified Ce 0.5 -Ti composite oxide catalyst, the particle size is 8nm, the specific surface area is 184m 2 / g, pore volume is 0.35cm3 / g, pore size is 18nm.

[0066] Comparative Example 1

[0067] The difference between Comparative Example 1 and Example 1 is only that:

[0068] Without modification, the prepared mesoporous Ce 0.3 -Ti composite oxide as catalyst.

[0069] Comparative Example 2

[0070] The difference between Comparative Example 2 and Example 1 is only that:

[0071] During the modification, SDBS was not used and the prepared mesoporous Ce 0.3 -Ti composite oxide was immersed in heteropoly acid solution. The prepared catalyst showed serious agglomeration phenomenon, the particle size increased to 30-50nm, and the specific surface area decreased to 162m 2 / g, pore volume is 0.32cm 3 / g, the pore size is 21nm, the active sites of catalytic reaction are reduced, and the catalytic activity is reduced.

[0072] Application Examples

[0073] The catalysts in the embodiments and comparative examples were applied to the coordinated purification of CVOCs and NOx. The specific application method and conditions were as follows: 150 mg of the prepared catalyst was loaded into a fixed-bed catalytic reactor, quartz wool was filled at both ends of the reactor to fix the catalyst bed, a mixed gas containing 50 ppm chlorobenzene and 500 ppm nitrogen oxides was prepared, and a gas mixture was introduced into the catalytic reactor at an air velocity of 60,000 h-1. A catalytic reaction was carried out at the catalytic temperature, and a gas chromatograph and a gas analyzer were used to monitor the concentration changes of chlorobenzene and nitrogen oxides before and after the reaction, respectively, and the catalytic conversion rate was calculated.

[0074] Table 1

[0075]

[0076] Table 2

[0077]

[0078] The results showed that the use of heteropolyacids such as H3PW 12 O 40 、H4SiW 12 O 40 、H3PMo 12 O 40 The cerium-titanium composite oxide catalyst modified with SDBS exhibits excellent synergistic catalytic activity against CVOCs and NOx.

[0079] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A heteropolyacid-modified cerium-titanium composite oxide catalyst, characterized in that: The invention uses a mesoporous cerium-titanium composite oxide as a carrier, and carries a composite modification layer of heteropoly acid and sodium dodecylbenzene sulfonate on the surface; the molar ratio of cerium to titanium in the mesoporous cerium-titanium composite oxide is (0.1-0.5):1; the molar ratio of heteropoly acid to sodium dodecylbenzene sulfonate in the composite modification layer is 1:(2-10); the heteropoly acid is H3PW 12 O 40 、H4SiW 12 O 40 、H3PMo 12 O 40 One of them.

2. The heteropolyacid-modified cerium-titanium composite oxide catalyst according to claim 1, characterized in that: The heteropolyacid-modified cerium-titanium composite oxide is obtained by immersing the mesoporous cerium-titanium composite oxide in a composite solution of heteropolyacid and sodium dodecylbenzene sulfonate and then performing heat treatment.

3. The heteropolyacid-modified cerium-titanium composite oxide catalyst according to claim 1, characterized in that: The particle size of the heteropolyacid-modified cerium-titanium composite oxide catalyst is 7 to 10 nm, and the specific surface area is 180 to 210 m 2 / g, pore volume is 0.3~0.5cm 3 / g, pore size is 10~20nm.

4. A method for preparing a heteropolyacid-modified cerium-titanium composite oxide catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) dissolving sodium dodecylbenzene sulfonate in water to obtain a SDBS solution; 2) dissolving the heteropoly acid in an ethanol aqueous solution to obtain a heteropoly acid solution, and adjusting the pH to 1 to 3; 3) under stirring conditions, adding the SDBS solution dropwise into the heteropolyacid solution to form a heteropolyacid-SDBS complex solution; 4) impregnating the mesoporous cerium-titanium composite oxide into the heteropoly acid-SDBS complex solution, stirring for reaction, separating the solid and the liquid, and drying the solid to obtain a catalyst precursor; 5) The catalyst precursor is heat-treated in an air atmosphere to obtain a heteropolyacid-modified cerium-titanium composite oxide catalyst.

5. The method for preparing the heteropolyacid-modified cerium-titanium composite oxide catalyst according to claim 4, characterized in that: The concentration of the SDBS solution is 0.01-0.1 mol / L; the concentration of the heteropoly acid in the heteropoly acid solution is 0.001-0.05 mol / L; in step 3), the stirring rate is 200-1000 r / min, the dropping time is 10-20 min, and the stirring is continued for 1-2 h after the dropping is completed.

6. The method for preparing the heteropolyacid-modified cerium-titanium composite oxide catalyst according to claim 4, characterized in that: The molar ratio of the heteropoly acid to titanium in the mesoporous cerium-titanium composite oxide is (0.05-0.2):1; in step 4), the stirring rate of the stirring reaction is 200-1000 r / min, and the reaction time is 4-24 h; the heating rate of the heat treatment is 2-5°C / min, the heat treatment temperature is 400-600°C, and the insulation time is 2-4 h.

7. The method for preparing the heteropolyacid-modified cerium-titanium composite oxide catalyst according to claim 4, characterized in that: The preparation method of the mesoporous cerium-titanium composite oxide comprises the following steps: a) dissolving a cerium source and a titanium source in an ethanol solution to obtain a cerium-titanium mixed solution; b) dissolving chitosan in acetic acid solution to obtain a chitosan solution; c) adding the cerium-titanium mixed solution dropwise to the chitosan solution under stirring, stopping stirring, heating until a uniform foaming gel system is formed, and drying to obtain a cerium-titanium composite oxide precursor; d) heat-treating the cerium-titanium composite oxide precursor in an air atmosphere to obtain a mesoporous cerium-titanium composite oxide.

8. The method for preparing the heteropolyacid-modified cerium-titanium composite oxide catalyst according to claim 7, characterized in that: The cerium source is one of cerium nitrate, cerium chloride and ammonium cerium sulfate; the titanium source is one of tetraethyl titanate and titanyl sulfate; the molar ratio of the titanium source to chitosan is 1:(1-5).

9. The method for preparing the heteropolyacid-modified cerium-titanium composite oxide catalyst according to claim 7, characterized in that: In step c), the stirring rate is 200-1000 r / min, the dropping time is 10-20 min, stirring is continued for 1-3 h after the dropping is completed, the heating temperature after stopping stirring is 60-80° C., and the heating time is 12-24 h; in step d), the heating rate of the heat treatment is 2-5° C. / min, the heat treatment temperature is 400-600° C., and the insulation time is 2-4 h.

10. Use of the heteropolyacid-modified cerium-titanium composite oxide catalyst according to any one of claims 1 to 3 in purifying CVOCs and / or NOx.